CML Developing Three Years after Therapy Completion in a Child with Ph(−) Pre-B-ALL - Hosseini, S.; Bahoush, G. H.; Vousogh, P.; Ansari, Sh.; Arjmandi, Kh.; Sabzechian, M. (Case Reports in Hematology, 2011)
We report a girl with a history of Ph(−) pre-B-ALL and three years of disease-free survival admitting to our hospital for regular end of treatment checkup with an increased white blood cell count which in follow-up studies and molecular detection of BCR-ABL (p210) fusions gene had been diagnosed as a Ph(+) typical CML. The upcoming question in this case scenario is whether developed CML is a secondary leukemia due to previous ALL chemotherapy or just a relapse case of primary leukemia.